Learning flat and pike entries during swim start from the block - Fischer, S; Kibele, A. (Biomechanics and Medicine in Swimming XI - Abstracts, 2010)
INTRODUCTION: A study with two randomly assigned subgroups was conducted to examine to effects of feedback information (entry angle) on the dive-in performance. While one group was instructed to perform a pike entry the other subgroup had to exercise a flat entry (i.e. Mills & Gehlsen, 1996; Maglischo, 2003). METHOD: Ten male elite swimmers participated in the study. Five starts were performed for each of four separate learning interventions. While the take-off phase was examined by an above-water video camera and portable starting block equipped with 2D-force strain gauges, the dive-in phase was examined with an under-water video camera. The starting performance was examined by the time elapsed between the starting signal and the passage of the head at 7,5 m. After each start, subjects received feedback information on their entry angle (angular displacement of the interconnecting line: finger tip vs. hip joint to the horizontal alignment). In addition, subjects were presented a slow motion video sequence of their take-off and dive-in behaviour. For the flat entry a entry angle of less than 35° was required. For the pike entry, subjects were asked to keep their entry angle above 40°. For the statistical analysis, kinematic parameters were used representing the take-off phase as well as the dive-in phase. For the latter, a new model was applied to reliably detect body landmarks despite air particles swept along the body surface during the dive-in phase and distorting clear vision. Dynamic parameters (maximal horizontal and vertical force values) completed the data analysis. The three best starts were included in the statistical analysis. An analysis of variance was used to identify statistical correspondences. RESULTS: Both subgroups improved their starting performance significantly. Subjects changed their take-off angle according to their required entry angles. Changes in the take-off angle, in the entry angle, and in the horizontal take-off velocity were statistically explained by the intervention factor and by the group factor. While the flat entry group improved their horizontal take-off velocity, no change in this parameter was observed for the pike entry group. However, the higher horizontal take-off velocity in the flat entry group was associated with less pronounced horizontal velocity during dive-in. The opposite effect was true for the pike entry group.